Precarização do trabalho e saúde dos trabalhadores terceirizados - Melo, Pamella Beserra de (2016)
The research presented here analyzed how the work affects the health of outsourced professionals working at the Federal University of Ceará (UFC). The research, based on the Clinic of Activity and located in the field of Worker’s Health, is based on qualitative epistemology and developed as a case study derived from intervention carried out in the UFC Central Warehouse. All the material produced in the intervention was used for the construction of the corpus pertaining to the case analyzed. Such a design corroborates the theoretical perspective mentioned for which the intervention is first performed, and then the research is started. It is acknowledged that each of these moments has different temporalities and objects, keeping a relation of mutual independence. The intervention comprised three stages: 1) formation of the analysis group, in which observations, interviews, documentary analyzes and filming were performed; 2) simple and/or cross self-confrontations, during which the workers were confronted with the audiovisual record of their activities; and 3) return to the initial group. The research methodology came from the videography method. To analyze the data, we used the constructive-interpretative content analysis of González Rey. The triple-directed activity (for the object, for the subject and for the other) was adopted as the unit of analysis. The relevance of the study is considered, since we are in a context marked by setbacks in the world of work, where archaic practices of management and control of labor and production coexist with “innovative” tendencies that weaken the working class, representing a threat to work on its ontological character and to workers’ rights. It is intended that the research contributes to the formulation of actions aimed at workers’ health and development of their power to act, as well as undressing the vulnerabilities to which workers with precarious employment ties are subjected. Thus, regarding the working conditions, it was perceived that workers with outsourced links are more subject to situations of vulnerability, and their work surrounding is permeated by situations of risk to their health and safety. It was noted that these professionals were more susceptible to situations of harassment, threat, disrespect, prejudice, authoritarianism due to the instability of the work bond; moreover they underwent inadequate conditions for the development of their activities, such as dusty, poorly lit and unventilated environment, with a precarious and old structure, as well as the lack of materials in good conditions and/or the use of inappropriate ones. Thus, it was observed that in the activity of the subjects studied several obstacles are imposed on their action, but through a model of participatory management they found the possibilities of developing their power to act and build health, strengthening the professional group that could recognize themselves as a group when discussing and debating the difficulties and possible suggestions for doing a job well done. It was also observed through the active participation of workers in the changes undertaken in the researched sector improvements such as redefining the duties and tasks of each worker, improvements in work processes to become more fluid and dynamic, holding systematic meetings with the participation and involvement of all professionals in the sector, listening to the suggestions and collectively questioning the issues at hand.